Morphological aspects of tympanic bulla after ventral osteotomy in cats - Silva, Adelina Maria da [UNESP]; Souza, Wilson Machado de [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Machado, Gisele Fabrino [UNESP]; Perri, Silvia Helena Venturoli [UNESP] (FapUNIFESP (SciELO), 2009)
To evaluate tympanic bulla healing after experimental ventral osteotomy in cats. Twenty adult cats were submitted to unilateral ventral bulla osteotomy and divided into two groups: cats of A1 group (n=10) were euthanized at 8 weeks and cats of A2 group (n=10), at 16 weeks postoperative. Signs of Horner's syndrome or damage to the inner ear were not found. Open-mouth radiographs taken in the immediate postoperative showed interruption in the contour of the larger compartment of the operated bulla. The result of Mcnemar'test was significant in A2 group (*p=0.0156). Macroscopic exams revealed that the operated bullae were similar to the normal ones, with preservation of the tympanic cavity. Connective tissue at the osteotomy site of the larger compartment was significantly found in the operated bullae in both groups (McNemar test: A1 p=0.0020*; A2 p=0.0078*). Histomorphometric analyses showed that the connective tissue length at the osteotomy site was shorter in A2 group than in the A1 group (Mann-Whitney test: p=0.0021*). Experimental ventral osteotomy did not alter significantly the tympanic bulla conformation and complete regeneration of tympanic bulla frequently did not occur before 16 weeks of postoperative period.

Objetivo: Avaliar a morfologia da bulla tympanica de gatos após osteotomia ventral unilateral. Métodos: Foram utilizados 20 gatos distribuídos em dois grupos de 10 animais cada, de acordo com o período de observação: A1 (8 semanas) e A2 (16 semanas). Resultados: Nenhum animal apresentou síndrome de Horner ou lesão do ouvido interno. Nas radiografias em projeção com a boca aberta realizadas no pós-operatório imediato observou-se a interrupção do compartimento maior da bulla tympanica operada, resultado significante no grupo A2 (McNemar, p=0,0156*). Os exames macroscópicos revelaram que a bulla tympanica operada apresentava conformação semelhante a da bulla tympanica normal, com preservação da cavidade timpânica. Na maioria das bullae tympanicae operadas observou-se a presença de tecido conjuntivo na área de osteotomia. O resultado do teste de McNemar foi significante em ambos os grupos (A1, p=0,0020*; A2, p=0,0078*). Os exames histomorfométricos demonstraram que a extensão de tecido conjuntivo presente no local da osteotomia do compartimento maior era menor nas bullae tympanicae operadas do grupo A2 (Mann-Whitney, p=0,0021*). Conclusões: A osteotomia ventral não alterou de maneira significativa a conformação da bulla tympanica. A regeneração total da bulla tympanica geralmente não ocorreu antes de 16 semanas de pós-operatório.
Aspectos morfológicos da bulla tympanica de gatos após osteotomia ventral
Keywords: Ear middle; Otitis media; Cats; Orelha Média; Otite Média; Gatos